Environmental Interpretation Program: an experience of the Biology School, Universidad de Costa Rica (Biocenosis, 2012)
Since its beginnings in Costa Rica, environmental interpretation has waxed and waned in its implementation, strategies, and objectives related to the conservation and management of protected areas, as well as to public recreation and site appreciation. A key aspect for the promotion and continuous improvement of environmental interpretation, especially in protected areas, is the training of interpretive professionals. Since 1991, the Biology School of the University of Costa Rica created the Environmental Interpretation degree, the only one in the Latin-American region. This paper describes the curriculum, as well as academic activities related to public use management and conservation of natural and cultural resources. Likewise it proposes alternatives to meet the challenges of environmental interpretation in Costa Rica.
Keywords: Biodiversity conservation; Protected areas; Environmental interpreters training